2019
DOI: 10.1016/j.jid.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel from Acellular Porcine Adipose Tissue Accelerates Wound Healing by Inducing Intradermal Adipocyte Regeneration

Abstract: As an important component of the skin, intradermal adipocytes are closely associated with skin homeostasis and wound healing. Although studies have focused on the role of fibroblasts, keratinocytes, and inflammatory cells in wound healing, the role of adipocytes has not been fully investigated. Here, we verified whether the induction of adipocyte regeneration in a wound bed can effectively promote wound healing, finding that the hydrogel from acellular porcine adipose tissue (HAPA) in combination with adipose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…29 Furthermore, SVF can provide an enhanced biological framework for adipocytes, thereby favoring adipose tissue survival. 30 These observations indicated that the combination of adipocytes and SVF might be an important factor in improving the efficacy of rejuvenation therapy. Certainly, many researchers also reported a similar positive effect of platelet-rich plasma (PRP) addition as an alternative approach in fat grafting.…”
Section: Discussionmentioning
confidence: 95%
“…29 Furthermore, SVF can provide an enhanced biological framework for adipocytes, thereby favoring adipose tissue survival. 30 These observations indicated that the combination of adipocytes and SVF might be an important factor in improving the efficacy of rejuvenation therapy. Certainly, many researchers also reported a similar positive effect of platelet-rich plasma (PRP) addition as an alternative approach in fat grafting.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, they can facilitate adhesion, survival, and differentiation of stem cells, as well as promoting host cell infiltration and revascularization ( Nie et al, 2015 ; Bankoti et al, 2020a ). Acellular matrices can be isolated from full skins ( Hsieh et al, 2020 ; Lin et al, 2020 ) and adipose tissues ( Dongen et al, 2019 ; Tan et al, 2019 ; Pu et al, 2020 ). In addition, acellular matrices are genetically tunable to adjust cell invasion through thrombospondin-2 knockout resulted in faster wound healing ( Morris et al, 2018 ).…”
Section: Fabrication Of Hydrogel For Wound Healingmentioning
confidence: 99%
“…Studies also showed that conditioned medium from cultured adipose-derived stem cells have the ability to promote tissue regeneration [21,22]. On the other hand, acellular adipose tissue as an important biomaterial, could also promote soft tissue regeneration [23,24].…”
Section: Introductionmentioning
confidence: 99%